2018
DOI: 10.1155/2018/3046576
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Effect of Structural Parameters on the Flexibility of Endovascular Stent Grafts

Abstract: The complication of stent graft-induced new entry (SINE) after thoracic endovascular aortic repair (TEVAR) may be caused by the spring-back force of both ends of the stent grafts. Spring-back force, which is exerted by the curvature and ends of stent grafts on the greater wall of the aorta, suggests poor flexibility. Research on stent graft flexibility via design optimization has been widely disregarded. Thus, this study investigates the relationship between stent graft structure and flexibility by measuring b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…A different approach examining the link between SG microstructure and flexibility based on its effect on stent graft-induced new entry (SINE) after thoracic endovascular aortic repair (TEVAR) was conducted by Guan et al [ 23 ], where stent spacing, apex angle, and strut configuration (Z- and M-shaped) were selected as structural parameters to investigate their effect on bending and spring-back forces. According to [ 23 ], optimizing SG flexibility can be achieved through enhanced stent spacing, a larger stent apex angle, and usage of z-stent shape over m-stent shape. Yan et al [ 24 ] suggested non-equal-strut stent hoops to improve radial support force and longitudinal flexibility, which were proven through numerical and experimental testing.…”
Section: Discussionmentioning
confidence: 99%
“…A different approach examining the link between SG microstructure and flexibility based on its effect on stent graft-induced new entry (SINE) after thoracic endovascular aortic repair (TEVAR) was conducted by Guan et al [ 23 ], where stent spacing, apex angle, and strut configuration (Z- and M-shaped) were selected as structural parameters to investigate their effect on bending and spring-back forces. According to [ 23 ], optimizing SG flexibility can be achieved through enhanced stent spacing, a larger stent apex angle, and usage of z-stent shape over m-stent shape. Yan et al [ 24 ] suggested non-equal-strut stent hoops to improve radial support force and longitudinal flexibility, which were proven through numerical and experimental testing.…”
Section: Discussionmentioning
confidence: 99%
“…A smaller aortic arch angle requires larger bending in the proximal stent graft to conform to the arch curvature. Spring back force, defined as the force applied by the stent graft to the greater wall of the aorta 42 increases in the smaller aortic arch angles. This leads to stent graft straightening and enlargement of the bird‐beak size.…”
Section: Discussionmentioning
confidence: 99%
“…The BCS was braided by 8 NiTi wires and 24 PET strips. The thickness of the PET strip was 0.12mm [12]. The width of the PET strip (w) was 0.57 mm, which could be calculated as following:…”
Section: Methodsmentioning
confidence: 99%
“…The BCS was braided by 8 NiTi wires and 24 PET strips. The thickness of the PET strip was 0.12mm [ 12 ]. The width of the PET strip ( w) was 0.57 mm, which could be calculated as following: where L is the distance of the two crossover points along the circumferential direction ( Figure 1a ).…”
Section: Methodsmentioning
confidence: 99%